Study of simple sequence repeat markers from coffee expressed sequences associated to leaf miner resistance - Pinto, Fernanda de Oliveira; Maluf, Mirian Perez; Filho, Oliveiro Guerreiro (Pesquisa Agropecuaria Brasileira, 2007)
The objective of this work was to identify expressed simple sequence repeats (SSR) markers associated to leaf miner resistance in coffee progenies. Identification of SSR markers was accomplished by directed searches on the Brazilian Coffee Expressed Sequence Tags (EST) database. Sequence analysis of 32 selected SSR loci showed that 65% repeats are of tetra-, 21% of tri- and 14% of dinucleotides. Also, expressed SSR are localized frequently in the 5'–UTR of gene transcript. Moreover, most of the genes containing SSR are associated with defense mechanisms. Polymorphisms were analyzed in progenies segregating for resistance to the leaf miner and corresponding to advanced generations of a Coffea arabica x Coffea racemosa hybrid. Frequency of SSR alleles was 2.1 per locus. However, no polymorphism associated with leaf miner resistance was identified. These results suggest that marker-assisted selection in coffee breeding should be performed on the initial cross, in which genetic variability is still significant.